Analysis of Patient Satisfaction with Food Services at Labuha Regional General Hospital, South Halmahera Regency, 2025 - Aswia Arsad; Agustin Rahayu; Musiana Musiana; Suryani Mansyur; Mayasari Soamole; Diah Merdekwati Surasno (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
Food service in hospitals is part of nutritional care that plays an important role in supporting the healing process of patients during treatment. The quality of food served to patients must not only meet nutritional standards, but also consider aspects of taste, hygiene, menu variety, food presentation, and timeliness of distribution. Patient satisfaction with food services is an important indicator in evaluating the overall quality of hospital services. Patients who are satisfied with the food provided tend to have a positive perception of the quality of hospital services and are more cooperative in undergoing treatment and hospital diets. This study aims to analyze the level of patient satisfaction with food services at Labuha Regional General Hospital in 2025. This study uses a quantitative design with an analytical survey approach. The sample in this study consisted of 89 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using the Chi-Square test with a significance level of α = 0.1. The results showed that most respondents were satisfied with the food service (56.2%). There was a significant relationship between patient satisfaction and food taste (p=0.000), food presentation (p=0.000), menu variety (p=0.000), food hygiene (p=0.000), cutlery hygiene (p=0.000), and timeliness of distribution (p=0.000). The conclusion of this study is that all factors studied have a significant relationship with patient satisfaction levels. Therefore, improving the quality of food service in hospitals is very important to support the healing process and overall patient satisfaction.